Plasma Chemical Synthesis of a Nanodisperse Titanium Dioxide Under the Influence of a Pulsed Electron Beam - Ponomarev D. V. Denis Vladimirovich; Remnev G. E. Gennady Efimovich; Sazonov R. V. Roman Vladimirovich; Kholodnaya G. E. Galina Evgenievna; Kochkorov B. Sh. Bolotbek Shakirovich (2010, 2010)
В фонде НТБ ТПУ отсутствует